Protective Effect of Caffeic Acid Phenethyl Ester on Cyclosporine A-Induced Nephrotoxicity in Rats - Gokce, Ahmet; Oktar, Sueleyman; Yonden, Zafer; Aydin, Mehmet; Ilhan, Selcuk; Ozkan, Orhan Veli; Yalcinkaya, Fatih Ruestue (Taylor & Francis Ltd, 2009)
Introduction. Cyclosporine A, an immunosuppressive agent, is widely used after organ transplantation such as the liver and kidney. However, its widespread use is restricted because it has serious toxic effects on the kidney. Caffeic acid phenethyl ester (CAPE) is a natural product with potent anti-inflammatory, antitumor, and antioxidant activities, and it attenuates inflammation and lipid peroxidation induced by ischemia-reperfusion injury. The purpose of the present study was to investigate the effects of CAPE on cyclosporine A (CsA)-induced nephrotoxicity. Material and Methods. Rats were divided into four groups and treated with saline, CAPE, CsA, and CsA + CAPE. Control rats were given saline; the CAPE group was given CAPE (10 mu mol/kg/day) for 11 days intraperitoneally; the CsA group was given CsA (15 mg/kg/day) for 10 days subcutaneously; and the CsA+CAPE group was given CAPE for 11 days, and rats were s.c. injected with CsA in 0.5 ml of saline once a day for 10 days at the same time. Results. The administration of CsA alone resulted in higher myeloperoxidase (MPO) activity, lipid peroxidation, superoxide dismutase (SOD), and catalase (CAT) than in the control. The enzyme activities except CAT in rats treated with CAPE alone were not changed. CAPE treatment prevented the increase in malondialdehyde (MDA) and increased CAT activity more, but did not affect the activities of MPO and SOD enzymes. Discussion. CsA causes renal injury and CAPE prevents CAT-and lipid peroxidation-mediated nephrotoxicity via inhibition of oxidative process.
Keywords: caffeic acid phenethyl ester; cyclosporine A; malondialdehyde; catalase; nephrotoxicity